2019
DOI: 10.3389/fpsyg.2019.02365
|View full text |Cite
|
Sign up to set email alerts
|

Red Light, Purple Light! Results of an Intervention to Promote School Readiness for Children From Low-Income Backgrounds

Abstract: Considerable research has examined interventions that facilitate school readiness skills in young children. One intervention, Red Light, Purple Light Circle Time Games (RLPL; Tominey and McClelland, 2011; Schmitt et al., 2015), includes music and movement games that aim to foster self-regulation skills. The present study (N = 157) focused on children from families with low-income and compared the RLPL intervention (SR) to a revised version of RLPL that included literacy and math content (SR+) and a Business-As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 77 publications
1
54
0
1
Order By: Relevance
“…There are many ways to stimulate children’s early self-regulation, and prior research has shown that social play ( Center on the Developing Child at Harvard University, 2011 ) as well as teacher-initiated games targeting self-regulation improves children’s self-regulation ( McClelland et al, 2019 ). However, as girls and boys are likely to select different activities when the learning environment is unstructured, the varying experiences could promote self-regulation differently in girls compared to boys.…”
Section: Discussionmentioning
confidence: 99%
“…There are many ways to stimulate children’s early self-regulation, and prior research has shown that social play ( Center on the Developing Child at Harvard University, 2011 ) as well as teacher-initiated games targeting self-regulation improves children’s self-regulation ( McClelland et al, 2019 ). However, as girls and boys are likely to select different activities when the learning environment is unstructured, the varying experiences could promote self-regulation differently in girls compared to boys.…”
Section: Discussionmentioning
confidence: 99%
“…A compromise between these options, however, could involve mentoring and coaching, which may expedite and strengthen educators' self-efficacy and fidelity in implementation. Indeed, there is ample evidence for the effectiveness of mentoring and coaching when attempting to influence the practices of the current educator workforce (Lambert et al, 2015), and this form of induction is a common feature of other curricular approaches (Barnett et al, 2008;McClelland et al, 2019). However, further research is needed to evaluate whether similar benefits would confer if applied to the PRSIST Program.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the Red Light, Purple Light Circle Time Games Program (Tominey and McClelland, 2011) organizes children into small-to-large playgroups for 20 min, twice per week, during which children play one of five group games that invoke self-regulatory challenge (e.g., doing the opposite of a natural response, such as dancing slow to a fast song). Evaluations have shown feasibility and benefit, such as increases in self-regulation for children initially low in self-regulation (Tominey and McClelland, 2011), and improvement in literacy (Tominey and McClelland, 2011;Schmitt et al, 2015) and math (McClelland et al, 2019). Other programs, such as Kids in Transition to School (KITS), have shown similar success when integrating selfregulation activities (as well as early literacy and prosocial skills) into group activities for children with developmental disabilities (Pears et al, 2015).…”
Section: Theoretical Model Of Self-regulation Changementioning
confidence: 99%
“…These interventions provide children with repeated opportunities to train on EF exercises or tasks, theorizing that short-term improvements in performance on an EF task will generalize to more global improvements in self-regulation (Posner et al, 2006 ). Programs use either direct EF tasks (often in more lab-based settings) or EF games (for e.g., Red Light/Purple Light; McClelland et al, 2019 ) to achieve this purpose. Studies demonstrate that training on a specific EF task may lead to improvements in task performance (Klingberg et al, 2002 ; McClelland et al, 2019 ; Scionti et al, 2020 ).…”
Section: Approaches To School-based School Readiness Interventions That May Promote Efmentioning
confidence: 99%